ESSENCE‐Q obtained in routine Japanese public child health check‐ups may be a valuable tool in neurodevelopmental screening. (21st October 2019) - Hatakenaka, Yuhei; Maeda, Masato; Ninomiya, Hitoshi; Hachiya, Koutarou; Fernell, Elisabeth; Gillberg, Christopher
Abstract: Aim: Our aim was to extend the validity of a questionnaire developed for screening and identifying early symptomatic syndromes eliciting neurodevelopmental clinical examinations‐questionnaire (ESSENCE‐Q) in young children. Methods: Early symptomatic syndromes eliciting neurodevelopmental clinical examinations‐questionnaire data for 207 children, living in Aki City, Japan, in 2014‐2015, were obtained from mothers, public health nurses and psychologists at 20‐ and 40‐month routine check‐ups at child healthcare centres. These were checked against subsequent ESSENCE diagnoses made by physicians. Receiver operating characteristic curves were constructed, and the area under the curves was compared. Sensitivity, specificity, positive predictive values (PPVs) and negative predictive values were calculated at optimal cut‐off values. The clinical utility index was also calculated. Results: When the ESSENCE‐Q was used by public health nurses, it demonstrated good validity, in terms of high sensitivity and high NPVs, at the 20‐month check‐up, but not at 40 months. Psychologists demonstrated good validity at both ages, but mothers did not. Good negative utility indexes, indicating screening accuracy, were obtained from the psychologists at both check‐ups and from nurses at 20 months. Conclusion: The ESSENCE‐Q results used by nurses and psychologists showed good validity. Future studies should confirm the effectiveness of this tool to identify children in need of clinical detailed neurodevelopmental assessment.